2018
DOI: 10.1590/1678-7757-2017-0495
|View full text |Cite
|
Sign up to set email alerts
|

The association between periodontal conditions, inflammation, nutritional status and calcium-phosphate metabolism disorders in hemodialysis patients

Abstract: ObjectivesTo analyze the association between periodontal conditions and inflammation, nutritional status and calcium-phosphate metabolism disorders in hemodialysis (HD) patients.Material and MethodsWe analyzed 128 HD patients divided into two groups: dentate (n = 103) and edentulous (n=25). The following items were assessed: baseline characteristics, age at the start and duration of HD, biochemical data: C-reactive protein (CRP), serum albumin, calcium, phosphorus, alkaline phosphatase, parathormone. A single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 28 publications
1
28
2
Order By: Relevance
“…However, in contrast to these results, there have been several reports indicating that PD patients and healthy individuals show a similar prevalence of periodontitis [7,8]. Surprisingly, a recent report suggested that 106 of 107 HD patients (99.1%) exhibit some form of periodontitis [9], and another study also showed that only one of 103 HD patients evaluated had a healthy periodontium [10]. Even if such reports are excluded, many studies have reported that over half of HD patients exhibit periodontitis [11,12,13,14].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, in contrast to these results, there have been several reports indicating that PD patients and healthy individuals show a similar prevalence of periodontitis [7,8]. Surprisingly, a recent report suggested that 106 of 107 HD patients (99.1%) exhibit some form of periodontitis [9], and another study also showed that only one of 103 HD patients evaluated had a healthy periodontium [10]. Even if such reports are excluded, many studies have reported that over half of HD patients exhibit periodontitis [11,12,13,14].…”
Section: Introductionmentioning
confidence: 94%
“…Thus, many studies have investigated the relationships between the prevalence and/or severity of periodontal disease and serum levels of inflammation-related factors in HD patients. Moreover, periodontal disease may also affect nutritional and bone loss parameters in HD patients [10,31]. Based on these reports, several researchers and clinicians have paid special attention to the relationship between periodontal disease and changes in systemic conditions, including inflammation, nutrition, and bone metabolism, resulting from HD.…”
Section: Hemodialysismentioning
confidence: 99%
“…The loss of dental tissue due to caries is less prevalent in individuals with CKD than when compared to the general population due to nausea, esophageal regurgitation or induced vomiting (in cases of bulimia nervosa). According to Cholewa [4], although there are inconclusive outcomes regarding the prevalence of caries in hemodialysis patients, most studies describe a high incidence of…”
Section: Discussionmentioning
confidence: 99%
“…Studies shows that the periodontitis in CKD patients was severe, with increased frequency in the presence of perio pathogens and showed in can be, though not always, observed in this group because of the lack of interdisciplinary care for these patients. Studies suggests that the higher prevalence of periodontal diseases was mainly caused by oral hygiene negligence, rather than by chronic uremia [4].…”
Section: Introductionmentioning
confidence: 99%
“…Phosphate metabolism is often dysregulated in chronic kidney disease (CKD), and hyperphosphatemia contributes to patient morbidity and mortality [48]. CKD is often comorbid with cancer [49], and an association of periodontal disease with CKD has been confirmed in observational studies [50,51,52]. As in cancer, it is plausible that the association of periodontal disease with CKD also involves dysregulated phosphate and calcium metabolism, seen in systemic CKD-MBD [53].…”
Section: Chronic Kidney Disease-mineral and Bone Disordermentioning
confidence: 99%